2019
DOI: 10.21565/ozelegitimdergisi.492808
|View full text |Cite
|
Sign up to set email alerts
|

Down Sendromlu Çocuğa Sahip Annelerin Aile Gereksinimlerinin Belirlenmesi ve Sosyal Destek Algılarına Yönelik Görüşleri

Abstract: Bu çalışmada Down Sendromlu çocuğu olan annelerin gereksinimlerinin belirlenmesi ve sosyal destek algılarına yönelik görüşlerinin incelenmesi amaçlanmıştır. Çalışmanın katılımcıları Gaziantep ilinde yaşayan Down Sendromlu çocuğa sahip 20 annedir. Nitel olarak desenlenen bu çalışmada yarı yapılandırılmış görüşme yoluyla annelerden elde edilen veriler içerik analizi ile değerlendirilmiştir. Çalışmada Down Sendromlu çocukların ve annelerinin toplumsal yaşamlarında sosyal kabul görmek istedikleri tespit edilmiştir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
2
0
0
1
Order By: Relevance
“…This can be due to the fact that state-funded services are perceived as insufficient. This finding confirms other studies that reported parents of children with DS found the EI service hours as insufficient and that they needed more educational support (e.g., Çiftçi, 2015; Gören, 2015; Toker, Başgül, & Özaydın, 2016). Contrary to the findings in our study, the results of several studies conducted in other countries reported that the majority of participating parents were satisfied with the EI services provided.…”
Section: Discussionsupporting
confidence: 91%
“…This can be due to the fact that state-funded services are perceived as insufficient. This finding confirms other studies that reported parents of children with DS found the EI service hours as insufficient and that they needed more educational support (e.g., Çiftçi, 2015; Gören, 2015; Toker, Başgül, & Özaydın, 2016). Contrary to the findings in our study, the results of several studies conducted in other countries reported that the majority of participating parents were satisfied with the EI services provided.…”
Section: Discussionsupporting
confidence: 91%
“…Especially for enrolment to the inclusive classes, principals and teachers are reluctant to accept the mentally disabled child in the educational environment. These findings also have similarity with the findings of researches of both Toker [38] and Genç [36]. Parents with mentally disabled children suppose that this reluctance derives from concern of principals of schools and institutes for deterioration of school atmosphere by the mentally disabled child.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…Selimoğlu, Özdemir, Töret ve Özkubat, 2013), down sendromlu (ör. Gören, 2015;Toker, Başgül ve Özaydın, 2019), serabral palsili (ör. Saygı, Giray, Cerşit, Ulutatar ve Aydın, 2015) çocuğa sahip aileler ile yapılmış araştırmalar karşımıza çıkmaktadır.…”
Section: Introductionunclassified